Evaluating sensitivity and specificity of the DPP Vet TB assay in badgers using Bayesian latent class models - Rachel C. Jinks; Sandrine Lesellier; Freya Smith; Fraser D. Menzies; Roland T. Ashford; Laura Waring; Dipesh Dave; Paul Anderson; Lesley A. Stringer; Ana V. Pascual-Linaza; David Corbett; Suzan Thompson; et al. (PLoS ONE, 2025)
In the UK and Ireland, the European badger is the main wildlife reservoir for Mycobacterium bovis (M. bovis), the causal agent of bovine tuberculosis (bTB). The ability to diagnose M. bovis infection in badgers is critical to understanding the epidemiology of the infection in this species and for informing control strategies. In this study we determined the sensitivity and specificity of a lateral flow assay (Dual Path Platform (DPP) VetTB assay) to identify infected live badgers using two blood sample types: fresh whole blood (suitable for immediate testing in the field without further processing) and serum (which can be stored frozen for batch testing). Two measures were used for the interpretation of test results: qualitative visual interpretation and quantitative measurement using an optical reader for a range of cut-offs. To overcome the absence of a gold standard comparison test, we used Bayesian latent class methods, applied to results from different sub-populations. Regardless of sample type, the highest sensitivity and specificity of the DPP under qualitative interpretation were obtained using Band 1 (MPB83 antigen) results. Median estimates (95% CIs) of sensitivity and specificity were 79.9% (66.1–91.4%) and 93.3% (90.7–95.7%), respectively for whole blood and 53.0% (43.0–63.7%) and 96.3% (94.7–97.7%), respectively for serum. Band 2 (ESAT-6/CFP-10), when interpreted on its own, had median sensitivity estimates of 21.4% (12.0–32.4%) for whole blood, and 6.8% (3.3–11.9%) for serum. When using Band 1 results from the optical reader, the estimate of sensitivity for whole blood was higher than for serum across the whole range of cut-offs, though with a concomitant reduction in specificity. This study provides reliable estimates of test characteristics for the DPP when applied to whole blood and serum. The results support the use of the DPP test in a field application to identify infected live badgers using whole blood samples.